Numerical study of binary mixture and thermal analysis near a solar radiative heated surface. (1st January 2022) - Khan, Mair; Salahuddin, T.; Khan, Qaisar; Al Alwan, Basem; Almesfer, Mohammad
Abstract: In this study, we present numerical and theoretical study of enthalpy and solar radiative heat transfer in a generalized Newtonian fluid flow induced by a flat plate. Our theoretical study depends on thermal diffusion coefficient, thermophoretic and viscous dissipation approach for modeling the steady boundary layer flow of heat and mass transfer over a flat surface. Impact of thermal diffusion coefficient with newly introduced enthalpy at heat and mass equations is considered. The boundary layer equations are transformed into system of ordinary differential equations by applying similarity variables and solved numerically by utilizing fifth-order Runge–Kutta integrator scheme with shooting technique. The physical results are explored by utilizing theoretical and numerical approaches. The numerical results acquired for different mechanisms are presented through tables and figures. The physical properties of the appearing parameters on the mean flow, temperature and concentration are presented through graphs and tables The comparative results are calculated for a limited case and good agreement is noted with previously published work. Highlights: Carreau fluid flow near a flat surface are investigated. Viscosity at initial steady state is discussed. Enthalpy and thermal diffusion coefficient are considered heat and mass equations. Thermophoretic effect is considered mass equation. Relationship between kinematic viscosity and intermolecular force is described.